Hellenic and Hellenistic Civilization: The Case between Exclusivity and Cultural Diffusion/Acculturation in Antiquity (2021)
Hellenic, which is synonymous to the culture of the Greeks in the Classical era; and Hellenistic civilization, which relates to the culture of post-classical Greek era have been discussed variously by Ancient and modem authors, noting their emergence and the consequences of the systems. This study, was therefore designed, to examine Hellenic structure and Hellenistic civilization, with a view to comparing both concepts in the classical and post-classical Greek world, Africa and the near East. The study argued that Hellenistic civilization served a greater purpose than the Hellenic system, due to the fact that it was more inclusive and so brought greater benefits to Greeks and non-Greeks. The Hellenic culture was exclusive to the Greeks. The study continued to argue that Hellenistic civilization, especially beginning from 323 BC, demonstrated some indices of cultural diffusion/acculturation that may have informed our modem assumptions on nationalism, imperialism and colonialism. The paper further argues that given an appropriate balance, cultural diffusion/acculturation whether deliberate or accidental, is an effective strategy for social development in given societies. The study adopts the comparative historical research as its methodology in examining the subject matter. Studies that may examine acculturation policies in ancient Rome and her provinces are recommended.